Diagnosis of abnormal body temperature based on deep neural network - Peng, Jinxiang; Zhang, Li (EAI Endorsed Transactions on Pervasive Health and Technology, 2022)
INTRODUCTION: A method for diagnosing abnormal body temperature based on deep neural network is proposed.OBJECTIVES: To improve the diagnostic accuracy, reduce the false alarm rate, and improve the diagnostic level of abnormal body temperature.METHODS: According to the weight of the temperature sensor node itself and its neighbor nodes, the network trust relationship is established, and the node trust value is output through the combination of decision-making. Use trust value and double threshold to identify and remove malicious nodes, and optimize the network structure. The optimized temperature sensor network is used to collect human body temperature data.RESULTS: A deep neural network is used to construct a diagnosis model of abnormal body temperature, so as to realize the diagnosis of abnormal body temperature.CONCLUSION: The experimental results show that the method in this paper has high diagnostic accuracy, low false positive rate and high diagnostic efficiency, and can improve the diagnostic level of abnormal body temperature.
Keywords: deep neural network; human body temperature; abnormal diagnosis; temperature sensor; malicious node